The mechanism underlying the effects of the cell surface ATP synthase on the regulation of intracellular acidification during acidosis - Wang, Wen-juan; Shi, Xiao-xing; Liu, Yi-wen; He, Yi-qing; Wang, Ying-zhi; Yang, Cui-xia; Gao, Feng (Journal of cellular biochemistry, 2013)
The F1F0 ATP synthase has recently become the focus of anti‐cancer research. It was once thought that ATP synthases were located strictly on the inner mitochondrial membrane; however, in 1994, it was found that some ATP synthases localized to the cell surface. The cell surface ATP synthases are involved in angiogenesis, lipoprotein metabolism, innate immunity, hypertension, the regulation of food intake, and other processes. Inhibitors of this synthase have been reported to be cytotoxic and to induce intracellular acidification. However, the mechanisms by which these effects are mediated and the molecular pathways that are involved remain unclear. In this study, we aimed to determine whether the inhibition of cell proliferation and the induction of cell apoptosis that are induced by inhibitors of the cell surface ATP synthase are associated with intracellular acidification and to investigate the mechanism that underlines the effects of this inhibition, particularly in an acidic tumor environment. We demonstrated that intracellular acidification contributes to the cell proliferation inhibition that is mediated by cell surface ATP synthase inhibitors, but not to the induction of apoptosis. Intracellular acidification is only one of the mechanisms of ecto‐ATP synthase‐targeted antitumor drugs. We propose that intracellular acidification in combination with the inhibition of cell surface ATP generation induce cell apoptosis after cell surface ATP synthase blocked by its inhibitors. A better understanding of the mechanisms activated by ecto‐ATP synthase‐targeted cancer therapies may facilitate the development of potent anti‐tumor therapies, which target this enzyme and do not exhibit clinical limitations. J. Cell. Biochem. 114: 1695–1703, 2013. © 2013 Wiley Periodicals, Inc.